A Case Study on Aggressive Behavior in Early Childhood from the Perspective of Parenting Styles and Social Environment - Muplihah, Gina; Puridawaty, Brigita; Mulyani , Wiwin; Hartati, Dini; Rahayu , Dwina Febrianti Sri; Lisnawati, Lisnawati (Kirana Publisher (KNPub), 2026)
This study aims to describe aggressive behavior and emotional regulation in early childhood as viewed from parenting styles and the child’s social environment. The research employed a qualitative method with a case study approach, utilizing observation, interviews, and documentation techniques. The findings indicate that the child exhibited both verbal and physical aggression, which were influenced by authoritarian parenting practices and a less supportive social environment. The child’s emotional regulation skills were found to be low, as evidenced by difficulties in expressing and controlling emotions. This study emphasizes the importance of responsive parenting and a positive social environment in reducing aggressive behavior and enhancing emotional regulation abilities in early childhood.